STATIC VERSUS DYNAMIC DEA IN FEDERAL HIGHER EDUCATION INSTITUTIONS - IFES - Costa, Edward Martins; Ramos, Francisco de Sousa; Souza, Hermíno Ramos de (Análise Econômica, 2014)
The present study aims to analyze intertemporal changes in productivity at Federal Higher Education Institutions (IFES) from 2004 to 2008. It examines efficient frontiers from each year using slacks-based (SBM-DEA) and dynamic slacks-based measures (DSBM) for data envelopment analysis (DEA). The total set of IFES was divided into two subsets (group A and group B) in order to minimize heterogeneity in the sector. Estimation results show that static frontiers for both groups underestimate the institution efficiency during the study period, indicating that intertemporal frontiers are more accurate when calculating efficiency since they consider a variable link between the inputs and outputs intertemporally.